Priorities for Sustainably Managing Sri Lanka’s Marine Fisheries, Coastal Aquaculture, and the Ecosystems that Support Them - World Bank (World Bank, Washington, DC, 2021)
The World Bank has engaged with the government of Sri Lanka in an advisory services and analytics (ASA) work entitled priorities for sustainably managing Sri Lanka’s marine fisheries, coastal aquaculture and the ecosystems that support them. The development objective of this ASA is to support the government in prioritizing investment and policy actions to enhance the welfare and resilience of coastal fishing communities and fisheries’ contribution to the national economy, including in light of the Coronavirus (COVID-19) pandemic and climate risks. This ASA forms part of the Bank’s support to the government in its effort to respond to, recover from, and build back better after the Coronavirus (COVID-19) pandemic, given the important role that the fisheries sector plays in the livelihoods of the coastal communities and food security of the nation as a whole. The government took swift measures to provide immediate relief and restore domestic fisheries production and the associated value chain in the first phase of the pandemic. For the recovery and build-back-better phases, the government is prioritizing sustainability and resilience, as well as infrastructure enhancement, adoption of innovative technology, institutional strengthening, and skill development to enhance productivity and global competitiveness as a means to generate employment and local value added and contribute to the balance of payments.